Development and Evaluation of a Web-Based App for Adverse Effect Management in Breast Cancer Patients Treated with Oral Targeted Therapy or Chemotherapy: Findings from a Pilot Study. - Lemieux, Julie; Côté, Isabelle; Lemay, Martine; Lauzier, Sophie; Després, Philippe; Desbiens, Christine; Doyle, Catherine; Poirier, Brigitte; Baghdadli, Amel; Di Schiavi Trotta, Leonardo; Nabi, Hermann (Current Oncology, 2026)
Simple Summary: This pilot study evaluated a web-based application developed to support patients with breast cancer receiving oral anticancer therapy in monitoring, managing, and reporting treatment-related side effects from home. Over a 13-week period, participants used the application to record daily symptoms and complete brief questionnaires regarding their well-being and treatment experiences. The findings indicate that both patients and healthcare professionals perceived the application as acceptable and feasible. Its use was associated with a reduction in telephone interactions with hospital pharmacists, suggesting a potential decrease in healthcare workload. Although no significant improvements were observed in treatment adherence-related measures, these preliminary results support the application's value as a supportive tool for patient self-management and communication. The insights gained from this pilot study may inform future research and guide the integration of digital health technologies into routine oncology care. This pilot study (NCT05743686) evaluated the feasibility of a web-based application enabling patients with breast cancer (BC) receiving oral therapy to self-report and manage treatment-related adverse effects (AEs). Patients were enrolled between January and August 2023. Historical controls were used for comparison. Participants used the web-app to self-report AEs daily for 13 weeks, completed the PRO-CTCAE weekly, and completed a questionnaire assessing psychosocial precursor factors associated with treatment adherence. Some patients and healthcare professionals participated in semi-structured interviews. The study included 28 participants and 185 historical controls. Compared with controls, participants had fewer interactions with hospital pharmacists (0 [0–1] vs. 0 [0–7], p = 0.04), with no significant differences in the number of visits, hospitalizations, or modifications to treatment. Concordance between AEs reported via the web-app and PRO-CTCAE was 66.2%. No statistically significant changes were observed in psychosocial precursor factors of treatment adherence following the intervention (all p > 0.05). The qualitative data underscored the generally positive reception of the web-based application among both patients and healthcare professionals. In conclusion, in this small mixed-methods pilot study, monitoring oral cancer therapy-related adverse effects using the web-app was feasible and acceptable, and was associated with a lower frequency of telephone contacts with hospital pharmacists compared with historical usual care. These preliminary findings are exploratory and warrant confirmation in larger, prospectively designed studies.